Acute Abdomen in Post-chemotherapy Acute Monoblastic Leukemia - Shih-Yi Lee; Jian-Hong Lin; Chuan-Tsai Lai; Kuo-Song Chang; Shou-Chuan Shih (International Journal of Gerontology, 2007)
A neutropenic patient with an acute abdomen could confuse the medical doctor in the decision making of whether or not a surgical intervention is essential to resolve the medical problem. Here, we report a 62-yearold female with acute monoblastic leukemia that was complicated by neutropenic fever and abdominal pain on the 13th day after receiving the first chemotherapy consisting of 1-beta-D-arabinofuranosylcytosine and idarubicin. Abdominal computed tomography revealed colitis involving the entire ascending colon. Neutropenic enterocolitis with Enterobacter cloacae septicemia was the final diagnosis. She received conservative management with close observation and recovered eventually. We discuss the etiologies of acute abdomen in patients receiving chemotherapy and their differential diagnosis.